EKOSISTEM KEWIRAUSAHAAN DAN KEWIRAUSAHAAN SOSIAL : SEBUAH PENELUSURAN LITERATUR UNTUK MEMAHAMI PERBEDAAN DAN PERSAMAAN KONSEP - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Iwan Setiawan (Universitas Galuh, 2023)
The concept of entrepreneurial ecosystem has an impact on social enterprises carried out by their actors, on the other hand, social entrepreneurs also influence the performance of the entrepreneurial ecosystem, encouraging the growth of new businesses that will also indirectly grow the entrepreneurial ecosystem in a region. This research focuses on seeing how the ecosystems of entrepreneurship and entrepreneurship complement each other or perhaps weaken each other. The entrepreneurial ecosystem has an important role in the development of social entrepreneurship, and vice versa, that social entrepreneurship can influence the development of an entrepreneurial ecosystem. The concept of the entrepreneurial ecosystem and social entrepreneurship has a positive feedback effect, strengthening each other, but not affecting each other linearly. Research opportunities regarding the ecosystem of entrepreneurship and social entrepreneurship are the development of methodologies to analyze a system more comprehensively. Qualitative methods in our opinion are suitable to be used to look at various relationships in a system such as this entrepreneurial ecosystem. Data and information obtained from qualitative techniques make it easier for researchers to understand the diverse characteristics of an entrepreneurial ecosystem, understanding the various dynamics that occur within them. Despite the differences, in principle, these two concepts appear to contribute positively to economic development and improve the welfare of the community.